(untitled) (ModaPalavra e-periódico, 2024)
The article aims to discuss the fundamental elements of fashion journalism as specialized journalism. By mapping academic production in journals, repositories and scientific databases, we produced a state of the art of fashion journalism studies in Brazil and worldwide published in three languages between 2011 and 2023. The results reveal that fashion journalism is considered specialized journalism, within what is called lifestyle. Presents similar functions to traditional journalism, fashion criticism, as well as providing services, advice, and entertainment; the characteristics of actuality, novelty and periodicity; the strength of opinion, the opinionated journalistic genre and the emphasis on image.